Radiological assessment of internal exposure resulting from ingestion of natural radionuclides in Arachis hypogaea L. grown in Turkey - Karataşlı, Muhammet; Turhan, Şeref; Abugoufa, A. H. A.; E, Goren; Kurnaz, A.; Hancerliogullari, A. (Codon Publications, 2019)
Groundnut (Arachis hypogaea L.) is one of the most important of all legumes and contains appreciable amounts of dietary oil and protein. Groundnut is added to many foods to enhance their levels of high-quality protein in diets lacking in nutrition. In this study, 51 groundnut samples were collected from the Mediterranean region of Turkey and analysed for naturally occurring radioactive isotopes of radium (226Ra), thorium (232Th) and potassium (40K). The activity concentrations of 226Ra, 232Th and 40K in groundnut samples varied from 2.9 ± 0.8 to 7.6 ± 1.0 Bq kg−1 (dw), with an average of 5.4 Bq kg−1 (dw); 4.4 ± 0.9 to 10.7 ± 1.2 Bq kg−1 (dw), with an average of 6.9 Bq kg−1 (dw) and 246.3 ± 18.2 to 541.8 ± 40.1 Bq kg−1 (dw), with an average of 427.1 Bq kg−1 (dw), respectively. The annual effective radiation dose was estimated to assess the health hazards caused by the ingestion of groundnut samples based on the measured activity concentrations of the radionuclides contained in them. The annual effective radiation dose varied from 6.5 to 10.1 µSv y−1, with an average of 8.3 ± 0.1 µSv y−1. The results revealed that consumption of Turkish groundnuts does not pose any radiological health hazards.
Keywords: Groundnut; Gamma-Ray Spectrometer; Annual Effective Dose; Natural Radioactivity; İnternal Exposure; Radiological Hazards; 2. Zero hunger